Implementación de un sistema de gestión de la calidad según la norma NTC-ISO 9001:2015 en la empresa Publiterm (2020)
This project seeks to implement a Quality Management System (SGC) according to NTC-ISO 9001: 2015 Quality Management Systems. Requirements in the PUBLITERM company so that in the future it is able to obtain the Quality certification, in addition it can bring traceability in its processes and Improve your performance.